Microplastic loads in fish and invertebrates in Malaysian rivers - Ng, Yong Sin (2023)
Microplastic pollution is a global problem, but little is known about the degree of microplastic contamination in tropical rivers, and even less is known of contamination levels in the animals in these systems. Additionally, there is a gap in knowledge regarding the extent of microplastic pollution in rapidly developing regions, where environmental infrastructure (e.g., sewage systems) and waste management are often inadequate. This study assessed the microplastic loads in invertebrates and fish in the Semenyih River, Malaysia. The Semenyih is a rapidly urbanising catchment on edge of Kuala Lumpur, Malaysia’s capital city. Microplastic contamination levels in river sediment and water were assessed at 8 sites along the river to develop a better understanding of the relations between environmental contamination levels and body loads of fish and invertebrates. Relations between body sizes and feeding preferences of animals were also examined. Microplastic loads in animals were assessed using two methods, one capable of detecting material in the 0.1-5 mm size range (low-resolution, manual microscopy), and the other down to 0.004 mm (semi-automated high-resolution, counterstaining dye method). Thus, microplastics including nanoparticles were assessed as part of this research.